MEMAHAMI EFEKTIVITAS PENERAPAN KEBIJAKAN TAX AMNESTY (PENGAMPUNAN PAJAK) DI INDONESIA - Letisya, Putri; Furqon, Ihmada Khori (Universitas Pembangunan Panca Budi, 2023)
Overcoming the problem of an increasingly weak economy, in this case the Indonesian government issued a new policy. As the author will describe, namely the Tax Amnesty policy. which aims to obtain tax revenue, which is expected to be able to increase tax revenue in Indonesia and change the tax system in Indonesia into a Self Assessment System, which previously used the Officeial Assessment System. The research method used by the author is the literature study method. In this regard, the author tries to describe and review the understanding of the effectiveness of the implementation of the tax amnesty policy. Where there is still very little for taxpayers who participate in this policy. Even though this policy also affects the compliance of each individual taxpayer.